Respiratory Variability during Different Auditory Stimulation Periods in Schizophrenia Patients - Akar, S. A.; Kara, S.; Bilgiç, V. (Methods of Information in Medicine, 2012)
Background: Schizophrenic patients are known to have difficulty processing emotions and to exhibit impairment in stimuli discrimination. However, there is limited knowledge regarding their physiological responsivity to auditory stimuli.Objectives: The purpose of this study was to compare the respiratory effects of two types of auditory stimuli with emotional content, classical Turkish music (CTM) and white noise (WN), on schizophrenia patients and healthy control subjects.Methods: Forty-six individuals participated in the experiment, and respiratory signals derived from a strain-gauge were recorded. Two important respiratory patterns, respiration rate and depth, were analyzed.Results: The results indicated that the patients presented a significantly higher respiration rate than control subjects during the initial baseline and WN exposure periods. Although CTM evoked an increase in respiration rates and a decrease in respiration depths in the control group, no significant differences were found during the stimulation periods in the patient group. The respiration rate was lower in the post-stimulation period than during the initial baseline period, and no respiration depth differences were found for the WN, music or post-stimulation periods in the schizophrenia group. Patients exhibited a greater respiration depth than the control subjects over all periods; however, a significant difference between the patient and control groups was obtained in the second resting condition and CTM exposure period. Furthermore, to analyze the effect of symptom severity on respiratory patterns, patients were divided into two classes according to their Positive and Negative Syndrome Scale score.Conclusions: Further studies are needed to correlate respiratory differences with emotionally evocative stimuli and to refine our understanding of the dynamics of these types of stimuli in relation to clinical state and medication effects.
Keywords: Schizophrenia; respiration depth; respiration rate; classical Turkish music; white noise